Vaginal microbiota in pregnant women with inflammatory rheumatic and inflammatory bowel disease: A matched case‐control study. Issue 8 (5th May 2021) - Rosta, Klara; Mazzucato‐Puchner, Antonia; Kiss, Herbert; Malik, Veronika; Mandl, Peter; Petricevic, Ljubomir; Foessleitner, Philipp; Shafran, Inbal; Temsch, Wilhelm; Farr, Alex
Abstract: Background: Rheumatic diseases and vaginal infections both increase the risk of preterm birth. It is unclear whether pregnant women with rheumatic disease are more likely to experience vaginal infections, which might potentially accumulate modifiable risk factors. Objective: In this study, we sought to evaluate the vaginal microbiota of pregnant women with inflammatory rheumatic and inflammatory bowel disease. Methods: A total of 539 asymptomatic women with singleton pregnancy were routinely screened for an abnormal vaginal microbiota between 10 + 0 and 16 + 0 gestational weeks. Vaginal smears were Gram‐stained and microscopically analysed. Those with inflammatory diseases (with or without immunomodulatory therapy) were assigned to the case group and matched in a 1:3 ratio to healthy pregnant controls. Results: Overall, an abnormal vaginal microbiota occurred more frequently among women of the case group, compared with those of the control group (33.8% vs 15.6%; 95% CI: 1.78–4.27, p < .001). In particular, Candida colonisation (22.3% vs 9.2%; 95% CI: 1.69–4.75, p < .001), but also bacterial vaginosis (14.9% vs 7.2%; 95% CI: 1.25–4.1, p = .006), occurred more often in the case than in the control group. No significant difference was found with regard to the occurrence of an abnormal vaginal microbiota between subgroups with and without immunomodulatory treatment (37.0% vs 27.1%; 95% CI: 0.29–1.35, p = .232). Conclusion: Pregnant women with inflammatory rheumatic and inflammatory bowel disease are at risk for bacterial vaginosis and Candida colonisation, which might pose a risk for preterm birth. Prospective studies are needed to further evaluate the influence of autoimmune conditions and immunosuppressive therapy on the vaginal microbiota.